Insulin Receptor Expression and Activity in the Brains of Nondiabetic Sporadic Alzheimer's Disease Cases. (16th May 2012) - Ho, Lap; Yemul, Shrishailam; Knable, Lindsay; Katsel, Pavel; Zhao, Rudy; Haroutunian, Vahram; Pasinetti, Giulio Maria
Abstract : We investigated the contents of the insulin receptor-beta subunit (IR β ) and [Tyr1162/1163]-phosphorylated IR β as surrogate indices of total IR content and IR activation in postmortem hippocampal formation brain specimens from nondiabetic sporadic Alzheimer's disease (AD) cases. We found no significant changes in the brain contents of total IR β or [Tyr1162/1163]-phosphorylated IR β, suggesting normal IR content and activation in the brains of nondiabetic sporadic AD cases. Moreover, total IR β and [Tyr1162/1163]-phosphorylated IR β levels in the hippocampal formation are not correlated with the severity of amyloid or tau-neuropathology. Exploring the regulation of glycogen synthase kinase 3 (GSK3) α/ β, key IR-signaling components, we observed significantly lower levels of total GSK3 α/ β in brain specimens from nondiabetic AD cases, suggesting that impaired IR signaling mechanisms might contribute to the onset and/or progression of AD dementia. Outcomes from our study support the development of insulin-sensitizing therapeutic strategies to stimulate downstream IR signaling in nondiabetic AD cases.